Best Answer

Why not? The statement is trivially true, meaning it holds for all values of x.

Q: Why the equation 7x plus 3 equals 7x plus 3?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

Double first equation: 10x + 2y = 10Subtract second equation: 7x = 7x = 1, y = 0

It is an equation and the value of x is 2

7x - 3 = 3 Subtract 3 from both sides: 7x - 6 = 0 So a = 7 and b = -6

x2+7x+3 = 0 Using the quadratic equation formula the solutions are:- x = -6.541381265 or x = -0.4586187349

Given 6x + (7x-8) = -5 6x + 7x - 8 = -5 ==> 13x = 3 therefore, x = 3/13

Related questions

Double first equation: 10x + 2y = 10Subtract second equation: 7x = 7x = 1, y = 0

It is an equation and the value of x is 2

7x - 3 = 3 Subtract 3 from both sides: 7x - 6 = 0 So a = 7 and b = -6

x2+7x+3 = 0 Using the quadratic equation formula the solutions are:- x = -6.541381265 or x = -0.4586187349

Given 6x + (7x-8) = -5 6x + 7x - 8 = -5 ==> 13x = 3 therefore, x = 3/13

22=7x+1 (take 1 of each side of the equals) 21=7x (divide each side by seven) 3=x (BAM! answer)

x2+7x+12=0usually this means to factor the equation.factored this equation would be...(x+3)(x+4)

y is increased by 7

you need to find the value of X first before you can solve this equation

-7x - 2y = -3

The answer to the math problem -3 7x plus 7 is x equals 1/3.

y=-10x-4